2019
DOI: 10.1371/journal.pone.0213744
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dysregulation between regulatory B and T cells (Breg and Treg) in human immunodeficiency virus (HIV)-infected patients

Abstract: This study examines the relationship between regulatory B (Breg) and T (Treg) compartments, which play crucial roles in the maintenance of immune homeostasis in the context of HIV. Using flow cytometry, the phenotypes of different Breg and Treg subsets from HIV-infected and healthy individuals were analyzed, along with the suppressive capacity of Breg. Peripheral blood samples of thirteen HIV + treatment-naïve individuals, fourteen treated-HIV + individuals with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In accordance with mouse data, studies in healthy donors and HIV patients found an enrichment of IL-10-producing cells within TIM-1 + B cells. In patients with HIV infection, TIM-1 + B cells specific for HIV antigens suppressed IL-17 and IFN-γ production by HIV-specific CD8 + and CD4 + T cells, which was partially reversed by IL-10 blockade ( 293 , 511 ). Human IL-10 + TIM-1 + Bregs can also be found infiltrating tumors and have been described to suppress CD8 + and CD4 + T cell anti-tumor responses ( 323 , 512 , 513 ).…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…In accordance with mouse data, studies in healthy donors and HIV patients found an enrichment of IL-10-producing cells within TIM-1 + B cells. In patients with HIV infection, TIM-1 + B cells specific for HIV antigens suppressed IL-17 and IFN-γ production by HIV-specific CD8 + and CD4 + T cells, which was partially reversed by IL-10 blockade ( 293 , 511 ). Human IL-10 + TIM-1 + Bregs can also be found infiltrating tumors and have been described to suppress CD8 + and CD4 + T cell anti-tumor responses ( 323 , 512 , 513 ).…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…Similarly, elevated levels of IL-10 producing B cells were observed in patients with HIV, HCV and lymphocytic choriomeningitis virus (LCMV) infections and the increased IL-10 levels were correlated with suppression of T cells [ 35 ]. Different methods of stimulation could impact the induction of IL-10 production by Bregs [ 9 ]. Upon stimulation with CpG-B, an agonist of TLR-9, we observed an induction of TGF- β expression on B cells and these TGF- β + B cells were enriched in acute hepatitis E patients compared to recovered individuals and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…We had further elucidated TGF-β1 as the regulatory molecule responsible for enhancement of Tregs in self-limiting HEV infection and use of TGF-β1 was suggested as a possible supplement for boosting Treg response towards recovery from severe hepatitis E [16]. IL-10 producing B cells are known to play a major role towards the induction and maintenance of Tregs [9]. Our current results definitely suggest participation of Bregs in the maintenance of immune homeostasis and may allude possible existence of Bregs-Tregs interactions in HEV disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, different immune cell populations that belong to the innate immune system (e.g. innate-suppressor cells of myeloid origin called myeloidderived suppressor cells (MDSCs)) and/or the adaptive immune system (adaptive-suppressor cells including regulatory T (Treg) cells and regulatory B (Breg) cells) work together in harmony to terminate inflammation and revert back to the homeostatic state [6,7,[17][18][19]. On the other hand, it is essential to keep in mind that although immunosuppressive cells could have a positive impact in the context of containing inflammation [20], especially if this is accomplished as soon as they become activated, failure to achieve such a goal could result in unwanted consequences, as seen in chronic inflammatory pathological conditions, such as observed in different types of cancer, certain autoimmune disorders and various infections [6,20].…”
Section: Introductionmentioning
confidence: 99%